2020
DOI: 10.1093/infdis/jiaa437
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental Sampling for Severe Acute Respiratory Syndrome Coronavirus 2 During a COVID-19 Outbreak on the Diamond Princess Cruise Ship

Abstract: A COVID-19 outbreak occurred in the Diamond Princess cruise ship and we sampled environmental surfaces after passengers and crews vacated the cabins. SARS-CoV-2 RNA was detected from 58 out of 601 samples (10%) from case-cabins 1-17 days after the cabins were vacated, but not from non-case-cabins. There was no difference in the detection proportion between cabins for symptomatic (15%, 28/189, Cq: 29.79-38.86) and asymptomatic cases (21%, 28/131, Cq: 26.21-38.99). No SARS-CoV-2 virus was isolated from any of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 15 publications
5
67
1
Order By: Relevance
“…Based on epidemiological data showing exclusive in-room transmission following imposed quarantine, as well as no correlation between infection patterns and central ventilation system, one research team concluded that close contacts and fomites were the main transmission routes (preprint article [79]). In support of this view, an environmental study failed to detect any virus in air samples despite widespread positive surface sampling; however, passengers had disembarked at the time of sampling (80). Conversely, a modelization study simulating the cruise ship outbreak found that the epidemic models which best predicted the empirical data suggested predominant short-range and long-range airborne transmission (preprint article [81]).…”
Section: Epidemiological Studies On Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on epidemiological data showing exclusive in-room transmission following imposed quarantine, as well as no correlation between infection patterns and central ventilation system, one research team concluded that close contacts and fomites were the main transmission routes (preprint article [79]). In support of this view, an environmental study failed to detect any virus in air samples despite widespread positive surface sampling; however, passengers had disembarked at the time of sampling (80). Conversely, a modelization study simulating the cruise ship outbreak found that the epidemic models which best predicted the empirical data suggested predominant short-range and long-range airborne transmission (preprint article [81]).…”
Section: Epidemiological Studies On Transmissionmentioning
confidence: 99%
“…This makes the results hard to generalize to most low-risk health care settings, such as long-term-care facilities. Negative results from air sampling studies in home and commercial settings (80,101), in the definite absence of AGPs, also add to the uncertainty. It is worth noting that when researchers modelized aerosol emission during normal breathing, the observed concentrations of airborne particles were low, frequently under the detection limit for most air sampling approaches (102).…”
Section: Air and No-touch Surface Samplingmentioning
confidence: 99%
“…Previous studies have suggested the heterogeneity in the cases on different decks and locations due to different transmission modes (Azimi et al 2020 ; Fang et al 2020 ; Plucinski et al 2020 ; Yamagishi et al 2020b ). The fomite and aerosol transmission (van Doremalen et al 2020 ; Mallapaty 2020 ; Mizumoto and Cowell 2020 ; Nakazawa et al 2020 ), and meteorological factors (Cheng and Wang-Li 2019 ; Hsiao et al 2020 ; Lin et al 2020 ; Pang et al 2020 ; Pani et al 2020 ) have been reported to make respective contributions to the spread of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 98%
“…The heterogeneity in SARS-CoV-2 transmission by deck was evaluated by using the data on total number of COVID-19 cases up to February 13th and the summarized information retrieved from data on the distribution of COVID-19 cases among passengers and crews onboard for each deck in the early period of COVID-19 outbreak on the Diamond Princess Cruise Ship published by Yamagishi et al ( 2020a , b ).…”
Section: Empirical Datamentioning
confidence: 99%
“…COVID-19 is highly infectious (basic reproduction number, R0, varying between 1.9 and 6.5 but typically between 2 and 3 [ 5 ]), exhibits a relatively long but infectious asymptomatic period [ 6 ], and is environmentally persistent [ 7 ]. SARS-CoV-2 has left hundreds of thousands dead, many permanently compromised, while many others have barely noticed their infection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%